Analisis Permasalahan Bullying Di Sekolah Dasar - Devana Devi Hoerunissa; Avivvah Sulistyowati; Gressia Fani Ekawati; Miftahul Jannah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Bullying in elementary schools is a serious problem that affects the social and psychological development of children. The purpose of this article is to examine bullying from various perspectives, such as its definition, forms (verbal, physical, and social), and its impact on victims. According to research, children who are victims of bullying are more likely to experience long-term mental health problems including anxiety and depression, which can have a negative impact on their social and academic lives. To create a safe and encouraging atmosphere, prevention initiatives involving character education, teacher preparation, and parent involvement are essential. Bullying in elementary schools is believed to be able to be reduced with everyone's cooperation, allowing children to grow to their full potential.